KEPASTIAN HUKUM BAGI KORBAN PENIPUAN JUAL BELI TANAH YANG BERSERTIPIKAT HAK MILIK: STUDI KASUS PUTUSAN NOMOR 873/PID/2021/PT SBY - Bayu Sangaji, Dimas; Prawesthi, Wahyu (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Land fraud involving certified ownership titles poses significant threats to legal certainty in Indonesia, with cases surging from 4,000 in 2021 to nearly 8,000 in 2025 per Ministry of ATR/BPN data. Enforcement under Article 378 of the Criminal Code prioritizes imprisonment over victim restitution, as evident in High Court Decision No. 873/Pid/2021/PT SBY, leaving victims without full recovery. This study aims to analyze legal certainty for victims of certified land sale fraud and propose restorative justice enhancements. It employs normative juridical research with statutory, case, and conceptual approaches. The population comprises relevant laws, doctrines, and court decisions; purposive sampling selects the aforementioned decision, KUHP Article 378, KUHAP Article 98, and supporting literature. Primary data from regulations and secondary from books/journals are analyzed qualitatively via description, classification, and legal syllogism. Findings reveal inadequate restitution integration, resulting in partial justice and prison overcrowding. In conclusion, restitution should be mandated as principal punishment in property crimes to balance retribution and restoration.